1978
DOI: 10.1097/00005072-197803000-00001
|View full text |Cite
|
Sign up to set email alerts
|

The Cytogenetic Basis for Classifying Ependymomas

Abstract: The phylogeny of ependymal cells and astrocytes can be traced to a single primitive progenitor the ependymoglia or the tanycyte, respectively. Ependymoglia cells have ependymal perikarya having astrocyte-like processes that terminate subpially in primitive glial footplates. Such cells prevail in primitive nervous systems, but they also persist regionally in the mature mammalian brain. Their fine structure has been studied in many species. An electronmicroscopic study of 8 ependymomas reveals that the neoplasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
85
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(88 citation statements)
references
References 0 publications
3
85
0
Order By: Relevance
“…It is also possible that the number of deletions is underestimated by the FISH technique (eg, small deletions or relative RB deletions in an extensively polyploid tumor). However, our frequencies of 9p and 13q losses are similar to those previously reported using other techniques 11,14,24,[32][33][34] and there appears to be no clear suggestion of a prognostic association based on the available data thus far. Therefore, it is probable that genes other than p16 and RB may be targeted by the 9p and 13q deletions in ependymomas.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…It is also possible that the number of deletions is underestimated by the FISH technique (eg, small deletions or relative RB deletions in an extensively polyploid tumor). However, our frequencies of 9p and 13q losses are similar to those previously reported using other techniques 11,14,24,[32][33][34] and there appears to be no clear suggestion of a prognostic association based on the available data thus far. Therefore, it is probable that genes other than p16 and RB may be targeted by the 9p and 13q deletions in ependymomas.…”
Section: Discussionsupporting
confidence: 82%
“…11,21,24,[31][32][33][34] Based on the recent finding of CGH detectable losses in high-grade examples, it was suggested that the RB pathway may be specifically targeted in the process of tumor progression. 24 In contrast, our larger study similarly identified a subset of ependymomas with 9p or 13q deletions by FISH, but there were no obvious associations with tumor grade, location, patients age, recurrences, or death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6) Only 27 cases of spinal subependymomas have been reported since 1954 (Table 1). [1][2][3][4][5]8,9,[11][12][13][14][16][17][18][19]21,23) The age of the patients ranged from 6 to 73 years, with the tumor found predominantly in men.…”
Section: Discussionmentioning
confidence: 99%
“…7) Normal tanycytes are long nonbranching unipolar or bipolar cells that extend between the ventricular surface and the cortex. 1,4,[10][11][12] Tanycytes in the spinal cord surround the central canal, and radiate from the ependyma of the central canal into the gray matter. 12) Although the origin of the tanycyte remains unknown, electron microscopy has identified features suggestive of secretion and/or chemical transportation.…”
Section: Introductionmentioning
confidence: 99%